2013
DOI: 10.1016/j.ymgme.2013.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of mitral valve disease in mucopolysaccharidosis VII dogs

Abstract: Mucopolysaccharidosis VII (MPS VII) is due to deficient activity of β-glucuronidase (GUSB) and results in the accumulation of glycosaminoglycans (GAGs) in lysosomes and multisystemic disease with cardiavascular manifestations. The goal here was to determine the pathogenesis of mitral valve (MV) disease in MPS VII dogs. Untreated MPS VII dogs had a marked reduction in the histochemical signal for structurally-intact collagen in the MV at 6 months of age, when mitral regurgitation had developed. Electron microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Concerning fibrosis of affected mice, collagen deposition was localized near the valves and at lower extent in the myocardium ( S3 Fig ). Many reports deal with an abnormal content or structure of collagen in cardiac tissues of MPS animal models and patients [ 2 , 8 , 25 26 , 28 32 ]. Our results are consistent with previous findings showing myocardial fibrosis in the murine models of MPS I [ 28 ] and MPS II [ 29 ], and the deposition of large amounts of collagen in the valves and myocardium of patients affected by Hurler syndrome [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Concerning fibrosis of affected mice, collagen deposition was localized near the valves and at lower extent in the myocardium ( S3 Fig ). Many reports deal with an abnormal content or structure of collagen in cardiac tissues of MPS animal models and patients [ 2 , 8 , 25 26 , 28 32 ]. Our results are consistent with previous findings showing myocardial fibrosis in the murine models of MPS I [ 28 ] and MPS II [ 29 ], and the deposition of large amounts of collagen in the valves and myocardium of patients affected by Hurler syndrome [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Neuropathology, skeletal and joint defects, and cardiac disorders are among the most prominent clinical manifestations of MPSs, which are refractory to the current therapies [106,108,109]. Although no studies are available in humans, investigations in animal models have shown a beneficial effect of CTS inhibition, especially in ameliorating cardiac disease in MPSs and other LSDs [161,162,171,173]. Since CTSs have also been shown to play a role in the onset and progression of neuropathology and skeletal disorders in MPSs, affected patients might gain benefits from treatments with CTS targeting-based drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The in vivo treatment of MPS I mice with a CTSB inhibitor reduced aortic dilatation and heart valve thickening, and led to an improvement of cardiac function, suggesting that CTSB inhibition may have a potential benefit in the disease [161]. Elevated activity of CTSB was detected in the MPS VII dog model showing abnormalities in the collagen structure of mitral valve [162]. When affected dogs received an intravenous injection of a retroviral vector expressing canine β-glucuronidase (the deficient enzyme in MPS VII), a reduced CTSB activity was observed, which correlated with an improved signal for structurally intact-collagen.…”
Section: Cathepsin Involvement In the Pathophysiology Of Mucopolysaccmentioning
confidence: 97%
“…Elastin fragmentation (white arrowheads) was more notable in (e) the coronary artery than the (f) aorta. Macrophages, the CD68 (brown) staining cells marked with m, were also abundant within the lesions of (g) the coronary artery and (h) aorta but devoid of lipid-laden vacuoles (Vogler et al 1994;Metcalf et al 2010;Bigg et al 2013) 28 years (Gniadek et al 2015) 28 min (gest age unknown) (Irani et al 1983) Stillborn (32 weeks' gest) (Molyneux et al 1997) 6 days (33 weeks' gest) (Geipel et al 2002) Fetal Not applicable (no animal studies).…”
Section: A Patient Consent Statementmentioning
confidence: 99%
“…Even amongst MPSs, MPS VII is a rare condition, affecting 1 in every 345,000-2,000,000 live births (Muenzer 2011). Sudden death has been described in two older patients, and corresponding reports of cardiovascular histopathology are also minimal (Vogler et al 1994;Metcalf et al 2010;Bigg et al 2013;Gniadek et al 2015). We describe the cardiovascular histopathology findings in a 11-year-old boy with MPS VII who died after sustaining ventricular tachycardia during a dental procedure under anesthesia, and relate the findings to findings in animal models of MPS VII that may shed light upon pathogenesis of MPSassociated cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%